The merits of playing it by the book: routine versus deliberate learning and the development of dynamic capabilities. (23rd May 2018) - Arndt, Felix; Fourné, Sebastian P L; MacInerney-May, Kieran
Abstract: In this study, we investigate the nature of dynamic capabilities and use a fine-grained measurement to test how centralization, routinization, and formalization relate to the underlying learning components of dynamic capabilities. We find that the effects of centralization, routinization, and formalization are broadly similar for almost all components of dynamic capabilities, and that only a few show a different pattern. Centralization and routinization are negatively related to dynamic capabilities, and formalization has a significantly positive effect. We provide insights into the role of managerial practices by explaining variation among the learning components of dynamic capabilities. This has implications for the nature and development of dynamic capabilities as well as for the routine versus deliberate learning debate.